2009
DOI: 10.1258/la.2008.008069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin-induced diabetes in domestic pigs with focus on the amino acid metabolism

Abstract: Streptozotocin (STZ) given intravenously destroys pancreatic beta cells and is widely used in animal models to mimic type 1 diabetes. The effects of STZ on the clinical state of health and metabolism were studied in six high health certified domestic pigs weighing 19 + 1.3 kg at the start of the experiment. A single STZ dose of 150 mg/kg of body weight successfully induced hyperglycaemia and alterations in amino acid metabolism. Within 9 h after STZ administration, the blood glucose values fell from 5.4 -7.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…After STZ injection the pigs showed polyuria/polydipsia, which was resolved by insulin treatment. Non-insulintreated STZ-diabetic pigs in the present study showed low DWG, in accordance with previous observations by Jensen-Waern et al 6 However, after the onset of insulin treatment, the DWG was at least as good as that of conventional high-health pigs.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…After STZ injection the pigs showed polyuria/polydipsia, which was resolved by insulin treatment. Non-insulintreated STZ-diabetic pigs in the present study showed low DWG, in accordance with previous observations by Jensen-Waern et al 6 However, after the onset of insulin treatment, the DWG was at least as good as that of conventional high-health pigs.…”
supporting
confidence: 93%
“…After acclimatization, the pigs underwent surgery and an indwelling silicon catheter (SIL-C70 with round tip; Instec Solomon, Plymouth Meeting, PA, USA) was inserted into their vena jugularis dexter under aseptic conditions. STZ was given intravenously according to Jensen-Waern et al 6 In brief, anaesthesia was induced with a combination of medetomidine (Domitor Õ vet, 1 mg/mL; Orion Pharma Animal Health, Sollentuna, Sweden) at a dose of 0.05 mg/kg BW, and tiletamine and zolazepam (Zoletil Õ , 250 mg/mL; Virbac, Reading, Carros, France) at a dose of 5 mg/kg BW intramuscularly.…”
Section: Experimental Designmentioning
confidence: 99%
“…The average blood glucose value of the T2DM group remained stable during the four‐month study period. We believe that the dosage (150 mg/kg) of the STZ injection was safe and could achieve balance in the damaged pancreatic β‐cells …”
Section: Discussionmentioning
confidence: 99%
“…27 To meet the criteria set by the World Health Organization for diabetes and to define diabetes, the fasting blood glucose level was measured, and an intravenous glucose tolerance test (IvGTT) was performed.…”
Section: The Induction Of Diabetes Mellitusmentioning
confidence: 99%